Facet joint injections for people with persistent non-specific low back pain (Facet Injection Study): a feasibility study for a randomised controlled trial - Ellard, DR; Underwood, M; Achana, F; Antrobus, JHL; Balasubramanian, S; Brown, S; Cairns, M; Griffin, J; Griffiths, F; Haywood, K; Hutchinson, C; Lall, R; et al. (NIHR Journals Library, 2017)
Background: The National Institute for Health and Care Excellence (NICE) 2009 guidelines for persistent low back pain (LBP) do not recommend the injection of therapeutic substances into the back as a treatment for LBP because of the absence of evidence for their effectiveness. This feasibility study aimed to provide a stable platform that could be used to evaluate a randomised controlled trial (RCT) on the clinical effectiveness and cost-effectiveness of intra-articular facet joint injections (FJIs) when added to normal care. Objectives: To explore the feasibility of running a RCT to test the hypothesis that, for people with suspected facet joint back pain, adding the option of intra-articular FJIs (local anaesthetic and corticosteroids) to best usual non-invasive care is clinically effective and cost-effective. Design: The trial was a mixed design. The RCT pilot protocol development involved literature reviews and a consensus conference followed by a randomised pilot study with an embedded mixed-methods process evaluation. Setting: Five NHS acute trusts in England. Participants: Participants were patients aged >= 18 years with moderately troublesome LBP present (> 6 months), who had failed previous conservative treatment and who had suspected facet joint pain. The study aimed to recruit 150 participants (approximately 30 per site). Participants were randomised sequentially by a remote service to FJIs combined with 'best usual care' (BUC) or BUC alone. Interventions: All participants were to receive six sessions of a bespoke BUC rehabilitation package. Those randomised into the intervention arm were, in addition, given FJIs with local anaesthetic and steroids (at up to six injection sites). Randomisation occurred at the end of the first BUC session. Main outcome measures: Process and clinical outcomes. Clinical outcomes included a measurement of level of pain on a scale from 0 to 10, which was collected daily and then weekly via text messaging (or through a written diary). Questionnaire follow-up was at 3 months. Results: Fifty-two stakeholders attended the consensus meeting. Agreement informed several statistical questions and three design considerations: diagnosis, the process of FJI and the BUC package and informing the design for the randomised pilot study. Recruitment started on 26 June 2015 and was terminated by the funder (as a result of poor recruitment) on 11 December 2015. In total, 26 participants were randomised. Process data illuminate some of the reasons for recruitment problems but also show that trial processes after enrolment ran smoothly. No between-group analysis was carried out. All pain-related outcomes show the expected improvement between baseline and follow-up. The mean total cost of the overall treatment package (injection 419.22 pound and BUC 264.00) pound was estimated at 683.22 pound per participant. This is similar to a NHS tariff cost for a course of FJIs of 686.84 pound. Limitations: Poor recruitment was a limiting factor. Conclusions: This feasibility study achieved consensus on the main challenges in a trial of FJIs for people with persistent non-specific low back pain.